Guardians Of Health: Periodontal Wellness and Its Impact on Systemic Diseases - A Questionnaire Based Survey Amongst Medical Professionals - Rohila, Pragati; Katoch, Samriti; Mittal, Sonal; Kaur, Avineet; Saini, Sarishti; Sharma, Parul (Journal of Neonatal Surgery, 2025)
Introduction: Periodontitis is a chronic inﬂammatory disease, characterized by progressive destruction of supporting periodontal structures. However, the periodontal infection can enter into the systemic circulation which may aggravate systemic diseases Aim: To perceive an understanding and knowledge among medical professionals on periodontal- systemic link with the help of a questionnaire based survey. Materials and Methods: The survey was conducted amongst medical professionals in Chandigarh tricity, India. There were a total of 15 questions in the questionnaire, and the respondents were asked to mark their appropriate choices. Results: A total of 150 medical professionals were involved in the study. In general as 73% of respondents were aware of the relationship between periodontal diseases and systemic health. Among the medical doctors practicing in Chandigarh tricity, this survey showed that knowledge about the relationship between periodontal health and general health was good. Conclusion: This study emphasizes on increasing the awareness regarding periodontal and systemic interrelationships amongst medical professionals